Parasitology and Microbiology Research - Antonio Bastidas Pacheco, Gilberto; Ali Kamboh, Asghar (IntechOpen, 2020)
The study of both unicellular and multicellular living beings and the diseases they produce from a biological point of view requires constant review of their relationship with their host and environment, given their indisputable sanitary importance. In this sense, in parasitology and microbiology, updated and concise information on life cycle, taxonomic classification, clinical manifestations, diagnosis, treatment, epidemiological behavior, and control measures is of vital importance. This is what we pursue with this book. The approach to parasitology and microbiology and the research that is carried out on it is unquestionable because the associations between life forms have been present from the very beginning of life.Research in parasitology and microbiology is necessary and indispensable for controlling diseases that affect much of the world with serious economic and social consequences. The challenge is to promote research to keep these diseases at bay. This book shows what has been done up to now and what can be done in the future to combat infectious diseases.